2020
DOI: 10.1111/1471-0528.16171
|View full text |Cite
|
Sign up to set email alerts
|

Cardio‐metabolic risk factors among young infertile women: a systematic review and meta‐analysis

Abstract: Background There is currently no concise systematic review or meta‐analysis addressing cardio‐metabolic risk factors in women experiencing infertility. Objectives To determine whether infertile women have higher levels of cardiovascular risk factors compared with fertile women. Search strategy We performed a systematic literature search using PubMed, Embase and CINAHL, Scopus and additional manual and bibliographic searches for relevant articles (end search date 6 November 2019). Selection criteria We selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
(80 reference statements)
0
18
0
6
Order By: Relevance
“…In addition to insulin resistance and hyperglycemia, also dyslipidemia, typical component of metabolic syndrome, has been suggested to have negative effects on fertility and pregnancy ( 32 ). A recent meta-analysis documented that infertile women had statistically significant higher BMI, increased total cholesterol, low-density lipoprotein (LDL)-cholesterol, and triglycerides compared to fertile women ( 33 ). A subgroup analysis revealed that total cholesterol, high-density lipoprotein (HDL)-cholesterol, fasting glucose, and fasting insulin were increased only in women with PCOS compared with fertile women, while BMI, triglycerides, and LDL-cholesterol were significantly increased in women with any cause of infertility relative to fertile women.…”
Section: Obesity and Fertility In Womenmentioning
confidence: 99%
“…In addition to insulin resistance and hyperglycemia, also dyslipidemia, typical component of metabolic syndrome, has been suggested to have negative effects on fertility and pregnancy ( 32 ). A recent meta-analysis documented that infertile women had statistically significant higher BMI, increased total cholesterol, low-density lipoprotein (LDL)-cholesterol, and triglycerides compared to fertile women ( 33 ). A subgroup analysis revealed that total cholesterol, high-density lipoprotein (HDL)-cholesterol, fasting glucose, and fasting insulin were increased only in women with PCOS compared with fertile women, while BMI, triglycerides, and LDL-cholesterol were significantly increased in women with any cause of infertility relative to fertile women.…”
Section: Obesity and Fertility In Womenmentioning
confidence: 99%
“…Besides, individuals with obesity, dyslipidemia or hypertension were also reported with a decrease in semen quality and changes in sex hormones. These might contribute to concomitant oxidative stress and inflammation, and impaired seminal antioxidant capacity (34,35). In this meta-analysis, we found a decrease of sperm total count, sperm concentration, sperm normal morphology, sperm progressive motility, and sperm vitality and an increase of sperm DNA fragmentation and MMP, while no significant difference was found in semen volume and sperm total motility.…”
Section: Discussionmentioning
confidence: 58%
“…Small sample size could increase the risk of sampling error, and thus lead to within-study and between-study heterogeneity and the expansion of synthetic effect size. Besides, the meta-analysis of continuous data usually showed a higher heterogeneity than categorical data, just like the recent study of "Cardio-metabolic risk factors among young infertile women: a systematic review and meta-analysis" (35).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 31 Furthermore, women with infertility are more likely to have cardiometabolic risk factors, such as atherogenic lipid profile and obesity, compared with fertile women. 32 Nevertheless, it remains challenging to determine whether the increased prevalence of adverse outcomes is attributable to the ART procedure itself 33 , 34 , 35 , 36 or maternal factors associated with infertility 37 or is multifactorial. 38 , 39 , 40 , 41 , 42 , 43 , 44 …”
Section: Discussionmentioning
confidence: 99%